2016
DOI: 10.1007/s11442-016-1334-8
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variation in annual actual evapotranspiration of terrestrial ecosystems in China: Results from eddy covariance measurements

Abstract: Abstract:Understanding the spatial variation in annual actual evapotranspiration (AET) and its influencing factors is crucial for a better understanding of hydrological processes and water resources management. By synthesizing ecosystem-level observations of eddy-covariance flux sites in China (a total of 61 sites), we constructed the most complete AET dataset in China up to now. Based on this dataset, we quantified the statistic characteristics of AET and water budgets (defined as the ratio of AET to annual m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 64 publications
3
17
0
Order By: Relevance
“…Meanwhile, annual values of the Priestley–Taylor coefficient ( a = ET/ET eq , 1.08–1.14, 1.37 in the growing season) and annual decoupling coefficient Ω (0.43–0.48, 0.61 in the growing season) evidently showed that the alpine meadow was under strongly energy‐limited condition (Li et al, ; Obojes et al, ; Priestley & Taylor, ). This finding is consistent with radiation energy availability ( Rn – G ) being the dominant factor controlling summer ET in alpine regions (Knowles et al, ; Yang et al, ; Zheng et al, ). Additionally, the much greater actual ET than reference ET in the growing season (Figure b) also suggested that ET was mainly controlled by the availability of evaporative energy (Sun et al, ; Williams et al, ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, annual values of the Priestley–Taylor coefficient ( a = ET/ET eq , 1.08–1.14, 1.37 in the growing season) and annual decoupling coefficient Ω (0.43–0.48, 0.61 in the growing season) evidently showed that the alpine meadow was under strongly energy‐limited condition (Li et al, ; Obojes et al, ; Priestley & Taylor, ). This finding is consistent with radiation energy availability ( Rn – G ) being the dominant factor controlling summer ET in alpine regions (Knowles et al, ; Yang et al, ; Zheng et al, ). Additionally, the much greater actual ET than reference ET in the growing season (Figure b) also suggested that ET was mainly controlled by the availability of evaporative energy (Sun et al, ; Williams et al, ).…”
Section: Discussionsupporting
confidence: 85%
“…Leaf area index (LAI) is an important variable affecting root zone soil water content and consequently ecosystem ET (Gu et al, ; Hurtalová, Usowicz, Kossowski, & Matejka, ; Shen et al, ) or may just be a proxy for the partitioning of ET into more plant transpiration and canopy interception than soil water evaporation under a dense canopy (Hu et al, ; McFadden et al, ; Zhu, Su, Li, Zhang, & Li, ). Moreover, the magnitudes of these controls vary with respect to vegetation types and timescales (Brümmer et al, ; Williams et al, ; Zheng et al, ). Therefore, understanding the interrelations of these covarying climatic and biotic determinants on ET variability remains challenging (Knowles et al, ; Ljungqvist et al, ; Obojes et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that annual net radiation, annual precipitation and annual mean temperature shaped the spatial pattern of ET, which provides a basis for assessing the spatial distribution of ET (Zheng et al, 2016). Network measured ET was also used to optimize the ET remote sensing model and to assess the spatial distribution of ET in China .…”
Section: The Spatio-temporal Variations Of Ecosystem Evapotranspiratimentioning
confidence: 97%
“…Investigating the spatio-temporal variations of ET and their influencing factors is of great significance for water resource management and assessment (Zheng et al, 2016). Eddy covariance technique can directly measure water vapor fluxes between atmosphere and biosphere Baldocchi, 2008), which plays an important role in exploring ET spatio-temporal variations and their affecting factors.…”
Section: The Spatio-temporal Variations Of Ecosystem Evapotranspiratimentioning
confidence: 99%
“…Evapotranspiration is the major component of water balance of the environment. In most terrestrial ecosystems, evapotranspiration is responsible for over 50% of the total water loss (Lu, Sun, McNulty, & Amatya, ; Zheng et al, ). During drought years or in regions where water is considerably limited, evapotranspiration is the most important component of the local water cycle and can comprise an even greater percentage of the total water loss (Jonard, André, Ponette, Vincke, & Jonard, ), which can equal or exceed precipitation (Wang et al, ).…”
Section: Introductionmentioning
confidence: 99%